2021
DOI: 10.4103/jrmt.jrmt_36_20
|View full text |Cite
|
Sign up to set email alerts
|

Radiology Request Form

Abstract: Introduction: Radiology request form (RRF) is a medical referral to a radiologist requesting input concerning the diagnosis, treatment, follow-up of patients, and intervention where necessary. The RRF usually provides information on the patient(s) and the investigation(s) being requested. Methodology: This was a cross-sectional descriptive study, in which request forms were retrospectively reviewed over a period of 6 months in the Radiology Department o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 7 publications
1
4
0
Order By: Relevance
“…CT-scans were requested to analyse major parts of the body, including: head [65.4% (public) vs 56.3% (private)]; chest [11.7% (public) vs 21.7% (private)]; and abdomen [14.5% (public) vs 9.2% (private)]. These results further enhance observations reported by studies from Zambia and Saudi Arabia[6,15].The partial completion of the referring physician information had been consistently reported in several studies[7, 16,17]. However, available studies require caution in interpretation because they do not estimate the risk of incomplete documentation of referring physician information.…”
supporting
confidence: 81%
“…CT-scans were requested to analyse major parts of the body, including: head [65.4% (public) vs 56.3% (private)]; chest [11.7% (public) vs 21.7% (private)]; and abdomen [14.5% (public) vs 9.2% (private)]. These results further enhance observations reported by studies from Zambia and Saudi Arabia[6,15].The partial completion of the referring physician information had been consistently reported in several studies[7, 16,17]. However, available studies require caution in interpretation because they do not estimate the risk of incomplete documentation of referring physician information.…”
supporting
confidence: 81%
“…On account of observed incomplete and incorrectly filled-in RRFs, the department decided to audit the adequacy https://dx.doi.org/10.4314/mmj.v35i2.7 of completion of general RRFs. In addition, the audit was supported by available literature that confirms that incomplete and incorrect filled-in RRFs negatively impacted the quality of medical imaging services 2,4,19,24 .…”
Section: Identification Of the Problem And Aim Of The Auditmentioning
confidence: 70%
“…A study by Zafar et al 21 though with a focus on RRFs for CT, found comparable results, where 72.34 % of RRFs in their study were also devoid of complete information relating to the patient identification. Robinson et al 24 and Whitley et al 3 emphasise the need for clinicians to provide adequate information, such as the patient's name. Besides, details such as gender and age are essential to the strengthening of the patient's identity 24 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations